2002
DOI: 10.1590/s1517-86922002000400003
|View full text |Cite
|
Sign up to set email alerts
|

Análise histológica e histoquímica das fibras dos músculos reto do abdome e intercostal paraesternal de ratos submetidos ao exercício da natação

Abstract: nos animais que nadaram durante 60 dias, aumento de fibras FOG para os que nadaram durante 45 e 60 dias e diminuição das fibras FG para os que nadaram durante 30, 45 e 60 dias. Dos fatos, pode-se concluir que, no exercício da natação os músculos inspiratórios realizaram maior trabalho devido à pressão hidrostática, aumento da freqüência respiratória e aumento da resistência elástica pulmonar, e que, para isso, houve a necessidade de maior adaptação aeróbica, com conseqüente aumento do percentual de fibras oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…In the same way, Saad et al (20) observed significant increase on the aerobic capacity in the straight muscles of the abdomen and in the paraexternal intercostalis muscles of rats submitted to swimming exercise as result of the increase on the percentile of SO fibers and decrease on the FOG fibers in rats that swam 60 days, five days/week in sessions of 60 minutes. On the other hand, the FG fibers increased in rats that swam 15 days, five days/week in sessions of 60 minutes.…”
Section: Discussionmentioning
confidence: 68%
“…In the same way, Saad et al (20) observed significant increase on the aerobic capacity in the straight muscles of the abdomen and in the paraexternal intercostalis muscles of rats submitted to swimming exercise as result of the increase on the percentile of SO fibers and decrease on the FOG fibers in rats that swam 60 days, five days/week in sessions of 60 minutes. On the other hand, the FG fibers increased in rats that swam 15 days, five days/week in sessions of 60 minutes.…”
Section: Discussionmentioning
confidence: 68%
“…The control rats had 20.8% slow contraction fibers (SO) and 79.2% fast contraction fibers (FOG + FG). Saad et al (2002) reports that control rats had 15.5% slow contraction fibers (SO) and 84.4% fast contraction fibers (FOG+FG). This difference is probably because each study sampled a different portion of the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, the load increase during the training was produced by the increase of the training time and not by external overload, as used in other articles (38)(39) . We believe that the increase of external load during the training could increment the changes observed, due to bigger overload that these animals would be submitted to.…”
Section: Discussionmentioning
confidence: 99%